Prescription Drug Misuse: Taking a Lifespan Perspective - Schepis, Ty S (Subst Abuse, 2020)
Prescription drug misuse (PDM), or medication use without a prescription or in ways not intended by the prescriber, is a notable public health concern, especially in the United States. Accumulating research has characterized PDM prevalence and processes, but age-based or lifespan changes in PDM are understudied. Given age-based differences in the medical or developmental concerns that often underlie PDM, it is likely that PDM varies by age. This review summarizes the literature on PDM across the lifespan, examining lifespan changes in prevalence, sources, motives and correlates for opioid, stimulant, and tranquilizer/sedative (or benzodiazepine) PDM. In all, prevalence rates, sources and motives vary considerably by age group, with fewer age-based differences in correlates or risk factors. PDM prevalence rates tend to decline with aging, with greater use of physician sources and greater endorsement of self-treatment motives in older groups. Recreational motives (such as to get high) tend to peak in young adulthood, with greater use of peer sources or purchases to obtain medication for PDM in younger groups. PDM co-occurs with other substance use and psychopathology, including suicidality, across age groups. The evidence for lifespan variation in PDM is strongest for opioid PDM, with a need for more research on tranquilizer/sedative and stimulant PDM. The current literature is limited by the few studies of lifespan changes in PDM within a single sample, a lack of longitudinal research, little research addressing PDM in the context of polysubstance use, and little research on minority groups, such as sexual and gender minorities.